Degenerative joint disease in cattle and buffaloes in the Amazon region: a retrospective study - Barbosa, José Diomedes; Lima, Danillo Henrique da Silva; Reis, Alessandra dos Santos Belo; Pinheiro, Cleyton Prado; Sousa, Melina G. S.; Silva, Jenevaldo Barbosa da [UNESP]; Salvarani, Felipe Masiero; Oliveira, Carlos Magno Chaves (Colégio Brasileiro de Patologia Animal - CBPA, 2014)
A retrospective study of the epidemiological and clinic-pathological aspects of cattle and buffaloes with degenerative joint disease (DJD) was conducted in the state of Pará, Brazil. From 1999 to 2014, eleven cattle and 24 buffaloes were evaluated. All the treated animals with suspected DJD underwent a clinical examination of the musculoskeletal system. In seven cattle and eight buffaloes with clinical signs of the disease postmortem examination was performed. The common clinical signs observed in both species were chronic lameness, stiff gait, postural changes, audible crackles in the affected limb, prolonged recumbency, difficulty in getting up and progressive weight loss. The lesions observed at necropsy were: irregular articular surfaces, erosion of the articular cartilage and the underlying bone tissue, and proliferation of the periarticular bone tissue with formation of osteophytes. The most affected joints in cattle and buffaloes wereof the hind limb. In buffaloes, the main predisposing factor to the onset of DJD was phosphorus deficiency. In cattle, defects of the anatomical conformation of the hind limbs, chronic trauma due to the activities performed, such as semen collection, and advanced age possibly contributed to the emergence of the disease.

Foi realizado um estudo retrospectivo sobre os aspectos epidemiológicos e clínico-patológicos em bovinos e búfalos com doença articular degenerativa (DAD) no estado do Pará, Brasil. Durante os anos de 1999 a 2014 foram avaliados 11 bovinos e 24 bubalinos. Todos os animais atendidos com suspeita clínica de DAD foram submetidos a exame clínico do sistema locomotor. Foram necropsiados sete bovinos e oito bubalinos com sinais clínicos da enfermidade. Os sinais clínicos comuns observados em ambas as espécies foram claudicação crônica, andar rígido, alterações posturais, crepitações audíveis no membro acometido, decúbito prolongado, dificuldade para levantar, e emagrecimento progressivo. As lesões articulares evidenciadas na necropsia consistiram em irregularidade da superfície articular, presença de erosão na cartilagem articular e no tecido ósseo subjacente, proliferação de tecido ósseo periarticular com formação de osteófitos. Tanto nos bovinos como nos bubalinos as articulações mais acometidas foram as dos membros posteriores. Nos bubalinos, possivelmente o principal fator predisponente ao surgimento de DAD foi à deficiência de fósforo, ao contrário dos bovinos, nos quais os defeitos de conformação anatômica dos membros posteriores, traumas crônicos em virtude da atividade exercida, como a coleta de sêmen e a idade avançada, foram o que, possivelmente, contribuíram para surgimento da enfermidade.
Doença articular degenerativa em bovinos e búfalos na Amazônia: estudo retrospectivo
Keywords: Amazônia; Búfalos; Bovinos; Claudicação; Doença articular; Osteoartrite; Amazon region; Cattle; Buffaloes; Lameness; Joint diseases; Osteoarthritis